Antecedents of withdrawing from announced acquisitions. - Woo, Kai Zhi. (2011)
This paper investigates the impact of board characteristics and CEO hubris on the withdrawal of acquisitions, an event less extensively investigated. Prior research indicates that board characteristics are associated with a firm’s financial performance, which is a direct consequence of the firm’s strategic decisions. Furthermore, executive hubris is found to influence corporate investment decisions such as acquisitions. Hence, we posit that board characteristics and executive hubris should have an effect on strategic decisions, specifically, acquisitions and their subsequent withdrawals. Using a conditional logistic model, we carried out the study on publicly traded U.S. firms. The results suggest a positive relationship between presence of a strategic committee and the likelihood of withdrawal from announced acquisitions. We also found a negative relationship between CEO hubris of acquirer and target firms with the likelihood of withdrawal. We conclude by discussing the implications of this study for practice and suggesting avenues for future research.